Analysis of Microstructures and Mechanical Properties of Particle Reinforced AlSi7Mg2 Matrix Composite Materials - Sahin, Ibrahim; Eker, Aysegul Akdogan (SPRINGER, 2011)
The present study examined the microstructures and mechanical properties (tensile and impact strength, hardness) of selected metal matrix composite materials. SiCp reinforced AlSi7Mg2 matrix composites were produced using gravity and squeeze casting methods and subsequently T6 heat treated. Some of the squeeze casted composites were shaped by extrusion. The extrusion generated an equiaxed matrix structure and SiCp caused a homogeneous distribution. The quasi absence of porosity in the squeeze casted composites led to improved mechanical properties. Whereas an increase in the SiCp ratio resulted in an increase of the tensile strength, it led to a decrease of the impact strength values. The enhancement of the mechanical properties following an applied heat treatment was better for materials shaped by extrusion.
Keywords: casting; extrusion; mechanical testing; metal matrix composites (MMCs); BEHAVIOR; ALLOY; CAST; DIE; Materials Science